Relationship among Lower Arch Length, Arch Width and Arch Perimeter in Crowding and Non-Crowding Groups - Selmani Mimoza; Gjorgova Julijana (Balkan Stomatological Society, 2015)
Crowding is one of the causes of class I malocclusion. The purpose of the present study was to examine the relationship between arch length, arch width and arch perimeter in crowded and non-crowded arches, as well as to made comparison of the right and left sides between them and to find out the contributing factor in lower arch crowding. The study groups consisted of 60 subjects aged 16 to 21 years. First group consisted of 30 pairs of dental study models with class I normal occlusion. The second group consisted of 30 pairs of study models with class I crowding. Measurements of arch length and width were made as defined by Lavelle and Foster, using Korkhaus callipers. Arch perimeter was measured by Lundstrom method's using manual calliper with sharp points. Differences between these measurements were made by Mann-Whitney U test (Z/U).